Skills Training for Cooking Contemporary Snacks Zuppa Soup for Santriwati in Islamic Boarding Schools in Deli Serdang Regency - Ramadhani, Sri; Nasution, Annio Indah Lestari (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2024)
Community Service activities are carried out by providing training in cooking contemporary snacks which are practiced directly by the experts. This activity was carried out as an effort to increase the understanding and skills of santriwati in pesantren by utilizing the natural potential they have to improve the welfare of santri in particular and pesantren in general. This PKM activity is packaged through pesantren economic empowerment by providing training in cooking contemporary snacks in the form of zuppa soup which is not only delicious but also healthy. The implementation is carried out starting from preliminary survey activities, providing motivation, and training which involves hands-on practice sessions, interactive discussions, and providing relevant training materials and materials. The results of this training are expected to provide participants with new skills in cooking contemporary snacks and increase their understanding of culinary business management. The training on cooking contemporary snacks is one of the efforts to increase economic independence among the community, especially in the pesantren environment. Contemporary snacks have a large market potential and can be a source of additional income for individuals and groups. This research aims to provide an overview of cooking training for contemporary snacks as a form of community service, especially in the pesantren environment